A new sea-nettle from the Eastern Mediterranean Sea: Chrysaora pseudoocellata sp. nov. (Scyphozoa: Pelagiidae) - Mutlu, Erhan; Çağatay, I. Tulay; Olguner, M. Tunca; Yilmaz, Hasan Emre (Zootaxa, 2020)
A new species of Chrysaora is described from five specimens collected off Turkey in the Eastern Mediterranean Sea during December 2018. The species is characterised by its pale exumbrella, milky to creamy in colour, bearing faint and narrow markings, strap-like marginal tentacles, semi-rounded to tongue-shaped lappets, and a prominent dark spot on the exumbrella above each rhopalium. Analysis of the COI gene indicates that it may be most closely related to Chrysaora africana (Vanhöffen 1902), from which it is nevertheless 10.2 % different. It is unclear whether the species represents a previously undetected and endemic species from the Mediterranean, or whether source populations are located in the Red Sea and the northern Indian Ocean.